12th Gawad CCP para sa alternatibong pelikula at video - Zulueta, Veronica (Animo Repository, 1999)
For the documentary category of the 12th Gawad CCP para sa Alternatibong Pelikula at Video, 2 entries by Lasallians shared 3rd place. Joel, ang Batang May Kanser by Veronica Zulueta and Guido Garayblas documented the life of Mark Ian Joel Acosta, a child with fibros sarcoma. The other winning film was Fifty-fifty by Karen Atizado and Eula Catimbuhan.